Penerapan Pendekatan Saintifik dalam Mengembangkan Berpikir Logis Anak Usia 5-6 Tahun di RA Takrimah Tungkop Aceh Besar - Dista, Fitrah Nabila (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2019)
The problems in Raudhatul Athfal Takrimah Tungkop Aceh Besar are children have not been able in the development of logical reasoning, laying out, spelling out, sorting objects and classification according to (size, shape, number, etc.), and drawing logical conclusions, which is related to logical thinking. The purpose of this study are: (a) To determine the development of logical thinking of children aged 5-6 years at RA Takrimah Tungkop Aceh Besar with a scientific approach and (b) To determine the ability of teachers to apply scientific approaches to develop logical thinking of children aged 5-6 years at RA Takrimah Tungkop Aceh Besar. The research conducted was Classroom Action Research. The results showed that (a) The development of logical thinking in cycle I was 39%, and an increase in cycle II with a percentage of 78%. (b) The ability of teachers to apply the scientific approach in the first cycle is 54%, and an increase in cycle II with a percentage of 80%. The final results of the study showed that the application of a scientific approach could develop logical thinking at RA Takrimah Tungkop Aceh Besar